Interaction with Artificial Intelligence as a Potential of Foreign Language Teaching Program in Graduate School - T. V. Potemkina; Yu. A. Avdeeva; U. Yu. Ivanova (Moscow Polytechnic University, 2024)
In  the  context  of  digitalization  of  educational  processes,  an  urgent  need  to  change approaches to teaching foreign languages in the training of highly qualified personnel  - future re-searchers has been growing. The focus of this article is to study and determine the state of the skill of interaction with digital tools, systems and programs of artificial intelligence in postgraduate students of technical fields. The study revealed a conflict between the growing importance of publications in English, and a general trend among learners to reduce the need to read scientific literature in English, which affects not only reading skills, but also affects scientific reading practices. The potential for resolving the identified contradiction lies in the development of pedagogical and methodological techniques  focused  on  the  inclusion  of  modern  digital  tools  in  the  educational  process  in  order  to develop higher-order cognitive skills in graduate students and optimize research processes related to working with English-language scientific literature. A concept of a course for teaching graduate students a foreign language using digital tools based on neural networks is proposed.